Conical and sabertoothed cats as an exception to craniofacial evolutionary allometry - Tamagnini, Davide (2023)
Among evolutionary trends shaping phenotypic diversity over macroevolutionary scales, CREA (CRaniofacial Evolutionary Allometry) describes a tendency, among closely related species, for the smaller-sized of the group to have proportionally shorter rostra and larger braincases. Here, we used a phylogenetically broad cranial dataset, 3D geometric morphometrics, and phylogenetic comparative methods to assess the validity and strength of CREA in extinct and living felids. To test for the influence of biomechanical constraints, we quantified the impact of relative canine height on cranial shape evolution. Our results provided support to CREA at the family level. Yet, whereas felines support the rule, big cats, like Pantherinae and Machairodontinae, conform weakly if not at all with CREA predictions. Our findings suggest that Machairodontinae constitute one of the first well-supported exceptions to this biological rule currently known, probably in response to the biomechanical demands and developmental changes linked with their peculiar rostral adaptations. Our results suggest that the acquisition of extreme features concerning biomechanics, evo-devo constraints, and/or ecology is likely to be associated with peculiar patterns of morphological evolution, determining potential exceptions to common biological rules, for instance, by inducing variations in common patterns of evolutionary integration due to heterochronic changes under ratchet-like evolution.